Structural Features that Govern Enzymatic Activity in Carbonic Anhydrase from a Low-Temperature Adapted Fish, Chionodraco hamatus. - S. MARINO; K. HAYAKAWA; K. HATADA; M. BENFATTO; L. BUBACCO; RIZZELLO, Antonia; MAFFIA, Michele (Biophysical Journal, 2007)
The carbonic anhydrase (CA) family of zinc metalloenzymes includes many known isozymes that have different subcellular distributions. The study described here focuses on identification of the structural features that define low-temperature adaptation in a Chionodraco hamatus protein, both for the reaction center, at an atomic level, and for the tertiary structure of the protein. To this aim, an x-ray absorption near-edge spectroscopy/Minuit x-ray absorption near-edge spectroscopy analysis of the reaction center was undertaken for both a structurally characterized human CAII and CA of C. hamatus. Higher structural levels were analyzed by sequence comparison and homology modeling. To establish whether the structural insights acquired in fish CAs are general, theoretical models were generated by homology modeling for three temperate-climate-adapted fish CAs. The measured structural differences between the two proteins are discussed in terms of the differences in the electrostatic potential between human CAII and CA of C. hamatus.We conclude that modulation of the interaction between the catalytic water molecule and the zinc ion could depend on the effect of the electrostatic potential distribution.